Determinants of strategic consistency of selected North American service firms - Rodriguez, Romualdo C.; Supangco, Vivien T. (Quezon City College of Business Administration, University of the Philippines Diliman, 2006)
The positive impact of strategic consistency on firm performance has been proven by previous research. However, little is known about what determines strategic consistency. To help fill that gap, this study evaluated the significance of potential determinants to strategic consistency. Strategic consistency is defined in this study as the firm's ability to adhere to and implement its strategic plans. Three categories of potential determinants were hypothesized to be positively associated with strategic consistency. The first category of factors evaluated is related to strategy implementation approaches. More specifically, the degree of collaboration and the degree of initiative initiative across organizational levels inherent in the strategy implementation approach adopted by the firm were evaluated. The second category of factors is related to the firm's environment, and included market turbulence, technological turbulence and competitive intensity. The third category of factors evaluated covered contextual factors, like the size of operations, and the adoption of technologies to enhance administrative effectiveness. Based on the results of a survey of 154 companies in North America, it was determined that both the degree of collaboration and the degree of initiative in the strategy implementation approaches adopted by a firm are positively associated with that firm's strategic consistency. The results did not support the hypotheses that environmental and contextual factors are significantly associated with strategic consistency. The managerial and theoretical implications of these findings are discussed.
Vita
Thesis (Doctor of Philosophy in Business Administration)--University of the Philippines Diliman
Keywords: Service industries -- Management. -- North America